2020
DOI: 10.1007/s12350-018-01513-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient motion correction for dynamic cardiac PET: Current status and challenges

Abstract: For dynamic cardiac PET of quantifying myocardial blood flow (MBF), patient motion is a major factor that affects the ROI definition and absolute quantification accuracy. In a recent study, an 82 rubidium ( 82 Rb)-dynamic-tailored motion-correction framework has been proposed to address the voluntary body motion for all the dynamic frames, including both early and late phases. 1 This approach brings us one step closer to the practical and full motion correction for dynamic cardiac PET studies. In this editoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Evidence supporting this is the far greater fraction of stress studies containing motion than rest studies. 22,23 Proper reconstruction of images when the heart has shifted with respect to the attenuating organs is non-trivial.…”
Section: See Related Article Pp 1104-1113mentioning
confidence: 99%
“…Evidence supporting this is the far greater fraction of stress studies containing motion than rest studies. 22,23 Proper reconstruction of images when the heart has shifted with respect to the attenuating organs is non-trivial.…”
Section: See Related Article Pp 1104-1113mentioning
confidence: 99%
“…Image artifact is an artificial finding in an image that should not be there, often leading to an incorrect interpretation and thus an incorrect diagnosis. Three well-documented types of motion artifacts in PET that lead to image artifacts are PET-emission-CTtransmission misregistration, 2-4 motion during dynamic acquisition [5][6][7][8][9] and motion due to breathing. [10][11][12] Emission-transmission misregistration happens when using the CT transmission from a PET/CT scanner to correct for attenuation of the 511 keV photons along the body during PET imaging.…”
mentioning
confidence: 99%
“…The effect of patient motion is largely that of inaccurate tracer distribution estimation due to a loss in spatial resolution as well as mis-alignment with PET emission data and corresponding attenuation correction map. 85 When the motion extent is relatively large compared to the spatial resolution of the scanner the effects become more severe which can potentially lead to degradation in image quality which affects the interpretation of the images and, possibly, misdiagnosis of the patient. 84 Moreover, as PET systems continue to advance with respect to hardware and reconstruction techniques the spatial resolution will continue to improve thus leading to greater influence of patient motion on image quality.…”
Section: Thesis Summarymentioning
confidence: 99%
“…For dynamic cardiac acquisition where absolute blood flow quantification is being performed patient motion can affect not only image quality, as described for MPI, but also the dynamic activity sampling within the blood pool and the myocardium. 85 Incorrect sampling due to patient motion often presents itself in the time-activity curves and manifests as discontinuities or spikes along the measured curves. 77 In a small clinical sample of seven patients, Yu and colleagues demonstrated that respiratory motion correction led to substantial increases in MBF and CFR, e.g.…”
Section: Thesis Summarymentioning
confidence: 99%
See 1 more Smart Citation